Polyethylene microplastics disrupt cardiopulmonary homeostasis via oxidative stress, inflammatory crosstalk, and mitochondrial dysfunction in Wistar rats - Kehinde, Samuel Abiodun; Olajide, Abosede Temitope; Ore, Ayokanmi; Olulana, Deborah Itunuoluwa; Tham, Chau Ling; Chusri, Sasitorn (Springer, 2026)
Polyethylene microplastics (PE-MPs) have emerged as ubiquitous environmental toxicants with systemic implications. This study investigated the mechanistic impact of PE-MPs on cardiopulmonary function, notably, the disruption of oxidative balance, inflammatory signaling, and mitochondrial metabolism. Male Wistar rats (with exception of control group) were orally administered PE-MPs at 15 and 60 mg/kg body weight daily for 28 days. Cardiopulmonary function, oxidative-inflammatory markers, and mitochondrial enzyme activities were assessed using standard biochemical assays. Concurrent increases in serum cardiac (cTnI, CK-MB, myoglobin) and pulmonary (IL-6, TNF-α, SP-D, KL-6) biomarkers indicate systemic inflammatory and injury signals following PE-MP exposure. Crosstalk between the heart and lungs was mediated by shared pathways, including redox imbalance marked by elevated NO and MDA levels and suppression of key antioxidants (CAT, SOD, MPO). Pulmonary metabolic enzymes (PFK, PK, LDH) were suppressed at the lower exposure level while several cardiac enzymes were perturbed only at the higher dose. This pattern may reflect organ-specific dose–response differences or greater pulmonary sensitivity, but does not establish temporal precedence or causal organ-to-organ signaling. Also, cardiopulmonary mitochondrial dysfunction was evidenced by inhibition of TCA cycle enzymes (CS, IDH, MDH, SDH) and respiratory chain complexes I–IV, with compensatory SDH and complex II upregulation in pulmonary tissue. Histological evaluation revealed a distinct, dose-dependent pattern of cardiopulmonary injury following PE-MPs exposure. These findings underscore the systemic vulnerability of the cardiopulmonary axis to PE-MPs, driven by oxidative–inflammatory interplay and metabolic collapse. The study highlights the need for integrative toxicological frameworks that account for organ crosstalk and environmental stressor synergy, advancing our understanding of microplastic-induced cardiopulmonary pathology.